1996
DOI: 10.2307/5738
|View full text |Cite
|
Sign up to set email alerts
|

Fishing and the Ground-Fish Assemblage Structure in the North-Western North Sea: An Analysis of Long-Term and Spatial Trends

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Animal Ecology. Summary 1. This paper examines long-term changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
1
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(122 citation statements)
references
References 28 publications
6
112
1
3
Order By: Relevance
“…Pauly et al 1998, Levin et al 2006, and fisheries may have played a role in the observed changes in the fish communities in the North Sea, Celtic Sea, and the area west of Scotland. The intensive exploitation of fish communities often leads to substantial reductions in the abundance of target species, in particular the larger predatory species, and changes in species composition (Greenstreet & Hall 1996, Rice & Gislason 1996, Daan et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Pauly et al 1998, Levin et al 2006, and fisheries may have played a role in the observed changes in the fish communities in the North Sea, Celtic Sea, and the area west of Scotland. The intensive exploitation of fish communities often leads to substantial reductions in the abundance of target species, in particular the larger predatory species, and changes in species composition (Greenstreet & Hall 1996, Rice & Gislason 1996, Daan et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…The diversity of each identified assemblage was calculated using Hill's index (N1) as a univariate measure of the species diversity (Hill, 1973). This index, which is the exponential of the Shannon-Wiener function (exp H'), has already been used in studies on fish assemblages (Greenstreet and Hall, 1996;Blanchard, 2001). Margalef's index (D) was used to assess the species richness of each assemblage.…”
Section: Analysis Of Abundance Datamentioning
confidence: 99%
“…These collapses typically followed long-term declines in abundance, such as those reported for North Sea cod (Cook et al 1997) and many tropical groupers (Epinephelinae) (Bannerot et al 1987). In contrast to these cases, some ¢shed stocks have continued to withstand high ¢shing pressure, and their abundance has increased in recent years (Daan 1996;Greenstreet & Hall 1996;Jennings & Kaiser 1998).…”
Section: Introductionmentioning
confidence: 99%